2015
DOI: 10.1016/j.plaphy.2015.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced extracellular production of trans-resveratrol in Vitis vinifera suspension cultured cells by using cyclodextrins and coronatine

Abstract: In the present work the effect of cyclodextrin and coronatine on both trans-resveratrol production and the expression of stilbene biosynthetic genes in Vitis vinifera L. cv Monastrell suspension cultured cells were evaluated. The results showed the maximum level of trans-resveratrol produced by cells and secreted to the culture medium with 50 mM cyclodextrins and 1 μM coronatine. Since the levels of trans-resveratrol produced in the combined treatment were higher than the sum of the individual treatments, a sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 37 publications
3
48
0
2
Order By: Relevance
“…We also observed that, in general, the detected increase of TPC with time was essentially independent of the presence or absence of CDs, reaching a maximum value of 233 ± 28 mg GAE per liter. The results are in agreement with previous results showing a negligible effect of HP--CD (20 mM) on the intracellular TPC in PSCC from M. citrifolia [14] and of M--CD (50 mM) on the intracellular TPC in PSCC from Linum usitatissimum [6], respectively. shows that, in the absence of CDs, the extracellular TPC barely increases upon along the days of culture, however, the determined values at a given time are always much lower than those of the intracellular TPC.…”
Section: Figures 2a and 2bsupporting
confidence: 93%
“…We also observed that, in general, the detected increase of TPC with time was essentially independent of the presence or absence of CDs, reaching a maximum value of 233 ± 28 mg GAE per liter. The results are in agreement with previous results showing a negligible effect of HP--CD (20 mM) on the intracellular TPC in PSCC from M. citrifolia [14] and of M--CD (50 mM) on the intracellular TPC in PSCC from Linum usitatissimum [6], respectively. shows that, in the absence of CDs, the extracellular TPC barely increases upon along the days of culture, however, the determined values at a given time are always much lower than those of the intracellular TPC.…”
Section: Figures 2a and 2bsupporting
confidence: 93%
“…The co-transport of glucosylated anthocyanidin and free GSH occurs in microsomes of yeast-expressing grapevine ABCC1, and leads to the conclusion that GSH conjugation is not an essential prerequisite for anthocyanin transport ( Francisco et al, 2013 ). In grapevine cells treated with MBCD or MBCD + MeJA, the similarity of the protein abundance profiles ( Martínez-Esteso et al, 2011b ) and gene expression ( Almagro et al, 2015 ) of STSs and GSTs has been noticed, and their coordinated action in the synthesis and transport of t -R, respectively, has been suggested.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of t -R and its non-glycosylated derivatives in grapevine tissues can be induced by biotic and abiotic (physical and chemical) elicitors (reviewed in Bavaresco and Fregoni, 2001 ; Bavaresco et al, 2009 ). In grapevine cell cultures, elicitor-induced t -R biosynthesis leads to the extracellular accumulation of this compound ( Liswidowati et al, 1991 ; Calderon et al, 1993 ; Krisa et al, 1999 ; Tassoni et al, 2005 ; Belhadj et al, 2008 ; Ferri et al, 2009 ; Yue et al, 2011 ), and is particularly abundant when cells are elicited with methylated cyclodextrins (MBCD), either alone ( Morales et al, 1998 ; Bru et al, 2006 ; Zamboni et al, 2006 ) or combined with the phytohormone methyl jasmonate (MeJA) ( Lijavetzky et al, 2008 ; Martínez-Esteso et al, 2009 , 2011b ; Belchí-Navarro et al, 2012 , 2013 ; Almagro et al, 2014 ), or its structural analog coronatine ( Almagro et al, 2015 ). Currently, there is no experimental evidence for the pathways that transport t -R to the extracellular medium in grapevine cells or any other plant system.…”
Section: Introductionmentioning
confidence: 99%
“…For example, 55-fold increased taxane production in Taxus x media cell cultures were achieved using cyclodextrin and methyl jasmonate (Sabater-Jara et al 2014). Nonetheless, even application of two different elicitors was also found effective, for instance 17-to 40-fold enhanced trans-resveratrol production in Vitis vinifera L. suspension culture cells using cyclodextrins and coronatine (Almagro et al 2015). Moreover, the application of different elicitors at suitable time intervals has enhanced secondary metabolite production more than the treatments in the same period.…”
Section: Open Accessmentioning
confidence: 99%